Sancho Panza y el carnaval salomónico (batucada barataria) - Campos Ocampo, Melvin (2006)
In the following pages we intend to demonstrate that the episode of the Barataria Island, in the Second Part of Don Quixote, is constructed as a parody of King Solomon, as told in the First Book of Kings, of the Bible. In order to accomplish this goal, our study is divided in two parts: a comparison of the two rulers (Sancho Panza and Solomon) and an analysis of the advices that Don Quixote gives Sancho, to prove they are parodies of the Proverbs by the so called “Wise King”.